Professional Accountants Codes of Ethics and the Public Sector Experience - Osagioduwa, Lucky Ogbomo; Ogbonmwan, Evelyn Ehizogie (The Journal of Accounting and Management, 2023)
This paper essentially investigated the extent to which professional accountants comply with the codes of ethics for professional accountants. Also, the research further investigated the level to which professional accountants employed and apply the codes of ethics in their real life business and conducts in the public sector of Nigeria. The research was conducted in four states in Nigeria. Two states in South-South Nigeria and two state in South-East Nigeria. Survey design was employed in this paper. Primary data were gotten through Five Likert Scale questionnaire administered. Auditors and accountant with two years and above years of working experiences were sampled. Systematic Sampling Technique (SST) was adopted. convenient sampling method was employed. Descriptive statistical techniques such as frequency distribution, charts, tables, and percentages response analysis were employed in analyzing the data. Cronbach Alpha Coefficient (CAC) was used to test for reliability of the research instrument. The hypotheses were tested engaging the Chi-square Analytical Techniques (CAT) and the ITpoint Analytical Techniques (ITAT). It was discovered that professional accountants significantly uphold integrity and objectivity codes of ethics in the Nigerian public sector. Also, it was discovered that professional accountant do not significantly employ and applies the codes of ethics in their real life transactions and conducts in the public sector of Nigeria. The study recommends among others that The Institute of Chartered Accountant of Nigeria should set up a monitoring committee to continuously investigate the level of members’ application of the codes of ethics in practical dealings with client and not on paper. Also recommended that regular seminal/workshop on professional accountant integrity in business practice should be organized by the IFAC globally and by professional accounting bodies n Nigeria.